High Stability Single-Port Dual Band Microwave Sensor Based on Interdigital Capacitor Structure With Asymmetry Branch Feedline - Syah Alam; Indra Surjati; Lydia Sari; Raden Deiny Mardian; Teguh Firmansyah; Muhammad Iqbal; Slamet Widodo; Mudrik Alaydrus; Zahriladha Zakaria (IEEE Access, 2025)
This paper proposes a single-port interdigital capacitor (IDC) resonator based on asymmetric branch feed line with high stability performance for permittivity detection of solid materials with a permittivity range of 1 - 6.15. The microwave sensor is designed using a single-port resonator operating at two different resonant frequencies $f_{r1} = 1.61$ GHz and $f_{r2} = 2.52$ GHz. Dual band frequency was proposed using asymmetric branch feed line. In addition, to confine the electric field concentration of the resonator, an interdigital capacitor (IDC) structure is proposed as a solution. Furthermore, a copper shield was proposed as conducting material to evaluate performance stability of the sensor from disturbance effect with range of $d = 1$ cm – 2.5 cm. Based on the measurement results, the sensor has high stability both without and with disturbance with an a Frequency Detection Resolution (FDR) of 0.009 - 0.4 GHz/ $Δ ε _{r}$ , a Normalized Sensitivity (NS) of 0.4% - 4.4%, and an average accuracy of 90% - 95% for both resonance frequencies, respectively. Therefore, this sensor can be recommended for several applications such as biomedical industry, pharmaceuticals and material quality control especially for outdoor measurements that are potentially affected by electromagnetic interference and disturbance.